Markups as a hedge for input price uncertainty: Evidence from Sweden - Sneha Agrawal; Abhishek Gaurav; Melinda Suveg (Research Institute of Industrial Economics (IFN), 2021)
In this paper, we study a new channel to explain firms' price setting behavior. We propose that uncertainty about factor prices has a positive effect on markups. We show theoretically that firms with higher shares of inputs with volatile prices set higher markups. We use the Bartik shift-share approach to empirically test whether firms which use more oil relative to other inputs set higher markups when oil prices are more volatile. Our estimates imply that a one standard deviation increase in oil price volatility leads to a 0.38 percent increase in the markup of firms with average oil exposure.
Keywords: D21; D22; D24; D42; D80; E31; E32; L11; L60; 330; price setting; markups; input price volatility; precautionary pricing